Morocco's Monetary Policy Transmission in the Wake of the COVID-19 Pandemic - Queyranne, Maximilien (IMF Working Papers; Working Paper ;, 2021)
This paper finds that the neutral interest rate has been on a downward trajectory in Morocco since the global financial crisis and may have fallen in the wake of the pandemic. In that context, monetary policy transmission to output and prices appears relatively muted given limited exchange rate flexibility until recently. Also, monetary policy transmission to some market rates has somewhat weakened in the wake of the pandemic. A lower natural rate and low policy rates raise the question of whether further rate reductions would impair the banking system. We find that the sensitivity of cash demand to deposit rates is low, implying limited risks that banks would lose funding with further reductions. A reliance on checking and savings accounts for funding may impair monetary pass-through, however. If monetary policy reaches its effective lower bound, limited and credible recourse to an asset purchase program could usefully complement conventional measures and strengthen monetary policy transmission under an inflation-targeting regime with a flexible exchange rate.